Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 21, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, February 21, 1930. Warner was abroad in 1891 and Hawley wrote to him on his return in late November. There were now two children in the Hawley family. The day, December 1, was the anniversary of the birth of "Bab," the older child. "She is a fine young woman of her age," Hawley wrote, closing his reminder of the occasion with the admonition "no presents." Scarcely a fortnight later Mrs. Hawley was obliged to submit to quite a serious operation. Familiar with hospitals and nursing herself, she was, her doctor said, "an ideal patient." Her "happy temper and high courage and her obedience" were "amazing," Hawley wrote Warner on December 16. The following was a presidential year (1892) and with it went the choice of a legislature which, at its session in 1893, would elect a United States senator, Hawley's term again expiring. He had, of course, a deep interest in the situation. The republicans renominated Benjamin Harrison and the democrats gave their third successive nomination to Grover Cleveland. General Merwin and Judge Luzon B. Morris were again the state candidates. This time Cleveland and Morris swept the state and Morris had a clearer majority overall.
1 electronic record. Scanned newspaper article. 1 image scans. 849 KB (870,259 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 18.6 MB (19,555,385 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Newspapers; Letters